Strength analysis of reinforced concrete in a closed space of a metal pipe - Pavlikov, Andriy; Kochkarev, Dmytriy; Harkava, Olga; Andriiets, Kateryna (Academic journal Industrial Machine Building Civil Engineering, 2020)
The concrete strengthening coefficient calculating method of concrete-filled steel tubular members at axial compression based on the plasticity theories by Saint-Venant and Huber-Mises-Genk. This method is used for calculating values taking into account the concrete meridional pressure on the pipe and axial stresses in it. The following tubular concrete element strength equation is obtained, where the stresses in the pipe reach the limit values at the element destruction moment, that is the materials strength is used completely. An calculation example is given and the strengthening coefficient calculation results are compared according to both theories. For determining the proposed method accuracy it is planned to compare the results of the calculation with experimental data